Answer:
c
Step-by-step explanation:
Y = -3x + 5
5x - 4y = -3
5x - 4(-3x + 5) = -3
5x + 4(3x) - 4(5) = -3
5x + 12x - 20 = -3
17x - 20 = -3
+ 20 + 20
17x = 17
17 17
x = 1
y = -3x + 5
y = -3(1) + 5
y = -3 + 5
y = 2
(x, y) = (1, 2)
Answer:
I do not see the model, but based on what you are telling me, I believe that both the fractions are equal is what is being shown. They are, in other words, equivalent fractions
Answer:
C
Step-by-step explanation:
Because of all the variables in the side lengths, we don't have enough information to use side-angle-side similarity.
We do have two angles of one triangle congruent to two corresponding angles of the other triangle, so we can use angle-angle similarity.
Sides AE and AD are corresponding sides. Sides AC and AB are corresponding.
Answer: C